MODIFIED WATER-CEMENT RATIO LAW FOR COMPRESSIVE STRENGTH OF RICE HUSK ASH CONCRETE (Nigerian Journal of Technology, 2017)
This work examines the modification of age long water – cement ratio law of Ordinary Portland Cement (OPC) concrete to cater for concrete with Rice Husk Ash (RHA). Chemical analysis of RHA produced under controlled temperature of 600°C was carried out. A total of one hundred and fifty (150) RHA concrete cubes at five different water/binder ratios and at six replacement levels of RHA (5%, 10%, 15%, 20%, 25%, 30%) were produced with specific attention given to cement/water (c/w) content and RHA/water (r/w) content. The cubes were subjected to compressive strength test at 56 days of curing producing a compressive strength in the range of 3.77 N/mm² to 34.04N/mm². A linear polynomial model was fitted into the experimental data using Minitab Package and was found adequate with an adjusted coefficient of determination of 73.0%.Test results show that the compressive strength of hardened RHA concrete depends on cement/water content by weight on one part and RHA/water content by weight on the other part. This indicates that the model equation is suitable to evaluate the compressive strength of RHA concrete at 95% confidence interval and the linear model has the capability of explaining the variability in the data by 73%.